ICC Jurisdiction: Against Israeli War and Humanitarian Crimes Targeting Palestinian Civilians 2023 - Soraya, Ninda; Muhammad, Ali; Ladiqi, Suyatno (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2000)
The article explains the jurisdictional policy of the International Criminal Court (ICC) regarding Israeli war crimes targeting Palestinian civilians, during the attack on Gaza on October 7, 2023. The article shows that based on articles of the Rome Statute, Israel committed war crimes and crimes against humanity that occurred on October 7, 2023. therefore, the ICC has authority in this matter. ICC policy towards conflict 7 October 2023, ICC jurisdiction took action to continue the investigative process and will accelerate investigations related to the conflict, while Israel in 2024 and the latest update is not part of the non-member states of the ICC. However, given the jurisdiction of the ICC, it has jurisdiction regarding its investigations in countries that are not parties to the ICC. This is influenced by several factors in upholding the ICC's jurisdictional investigation law against Israeli criminals even though Israel is not an ICC member state: First, Palestine is a state party to the ICC which is supposed to provide justice for civil society. Second, there is pressure and encouragement from member countries and non-member countries of the ICC to carry out investigations regarding the conflict attack in October 2023.